Cost-Return Budgets–Irrigated Crops - Langemeier, Larry N.; Whitney, David A. (My University, 1998)
This publication utilizes specific input values and/or rates for seed, insecticide, herbicide, and fertilizer based on a given yield level to provide information for producers with irrigated crops.
MF941_1998_10
Keywords: MF941; Economics; Crops; MF